Health poverty alleviation in China from the perspective of historical institutionalism: policy changes and driving factors - Xu, Li; You, Xiaojian; Cui, Yinan; You, Jiali (Frontiers in Public Health, 2024)
Health poverty alleviation is an effective tool for improving the living quality and developmental conditions of impoverished populations. Since 1978, China has been actively implementing health poverty alleviation projects, resulting in a more robust rural healthcare service network and increased convenience for the local population to access medical treatment. However, it is crucial to acknowledge that China still faces a complex situation with the simultaneous existence of multiple disease threats and the interweaving of various health influencing factors. Ongoing risks of emerging infectious diseases persist, and some previously controlled or eliminated infectious diseases are at risk of resurgence. The incidence of chronic diseases is on the rise and exhibits a trend toward affecting younger populations. Therefore, examining the successful experiences of China's health poverty alleviation over the past 40 years becomes a critically important issue. The study focuses on China's health poverty alleviation policies, employing historical institutionalism as a theoretical perspective to analyze the historical changes and evolutionary logic of health poverty alleviation policies. A historical institutionalist analytical framework for health poverty alleviation policies is constructed. The research findings reveal that China's health poverty alleviation policy has undergone three distinct periods since 1978: the initial phase (1978–2000), the exploratory phase (2000–2012), and the stable development phase (2013–present). At the macro level, the political, economic, and social contexts of different periods have influenced the evolution of health poverty alleviation policies. On the meso level, coordination effects and adaptive expectations have had an impact on China's health poverty alleviation policy. At the micro level, various actors, including the central government, local governments at different levels, social forces, and impoverished communities, interact during the evolution of health poverty alleviation policies. This paper summarizes the theoretical aspects of China's health poverty alleviation policy experience. The research conclusions, viewed through the lens of historical institutionalism, offer practical insights into the evolution of government policies. This provides directional guidance for enhancing health poverty alleviation projects.